B-cell depleting therapies may affect susceptibility to acute respiratory illness among patients with multiple sclerosis during the early COVID-19 epidemic in Iran - Safavi, Farinaz; Nourbakhsh, Bardia; Azimi, Amir Reza (Multiple sclerosis and related disorders, 2020)
•4.8% of MS patients fulfilled defined criteria for COVID-19-suspect group.•Two patients required hospitalization; no intubation or ICU admission was reported.•Patients on B-cell depleting agents had higher risk of being in the COVID-19-suspect group. To determine whether the course of COVID-19 is more severe in patients with MS and if MS disease-modifying treatments (DMTs) affect the risk of contracting the disease. In a cross-sectional survey, data were collected by sending a questionnaire to 2000 patients with a demyelinating disease through an online portal system. Collected data included the current MS DMT and patient-reported disability level, history of recent sick contact, recent fever, respiratory symptoms, diagnosis with COVID-19, and the disposition after the diagnosis. We defined a COVID-19-suspect group as patients having fever and cough or fever and shortness of breath, or a presumptive diagnosis based on suggestive chest computed tomography. We calculated the proportion of COVID-19-suspect patients and compared their demographics, clinical characteristics, and DMT categories with the rest of survey-responders, using univariable and multivariable models. Out of 712 patients, 34 (4.8%) fulfilled our criteria for being in the COVID-19-suspect group. Only two patients required hospitalization. No patient required intensive care. In a multivariable model, disease duration (p-value=0.017), DMT category (p-value=0.030), and history of sick contact (p-values<0.001) were associated with the risk of being in the COVID-19-suspect group. Being on B-cell depleting antibodies (as compared to non-cell depleting, non-cell trafficking inhibitor DMTs) was associated with a 2.6-fold increase in the risk of being in the COVID-19-suspect group. (RR: 3.55, 95%CI: 1.45, 8.68, p-value=0.005). The course of infection in patients with MS suspected of having COVID-19 was mild to moderate, and all patients had a full recovery. B-cell depleting antibodies may increase the susceptibility to contracting COVID-19.